PENGARUH IKLIM ORGANISASI DAN MOTIVASI TERHADAP KINERJA TENAGA PENGAJAR PADA CV PERISAI SAINS PALEMBANG - Djatmiko Noviantoro (JURNAL KOMPETITIF, 2017)
The purpose of this study was to determine and analyze how much influence the organizational climate and motivation on the performance of teaching staff at CV Perisai Sains Palembang. CV Perisai Sains Palembang is an institution which is engaged in non-formal education, in the form of courses (Mathematics, English, and accounting) for children of school age (elementary through high school).The method used in this research is the survey approach. This type of research is quantitative descriptive, and the nature of his research is the explanation. The analytical method used is multiple linear regression.The conclusion that can be drawn from the test results indicate that the organizational climate and motivation simultaneously influence the performance of teachers in CV Perisai Sains Palembang. Based on this, the agency should establish a good organizational climate. This can be done by developing relationships and good communication among faculty, and between faculty with leadership. In addition, agencies must be increase the motivation of the teaching force as an effort to improve the performance of teachers. Motivation can be administered in the form of additional incentives to faculty who good performance. Keywords: organizational climate, motivation, performance.